A General Outlook on Turkish Librarianship and Libraries - Çelik, Hilmi; Bayır, Didar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Turkey has a rich book and library tradition going back centuries. This article presents an overview of Turkish libraries and librarianship by providing information specifically on the library tradition in Turkey, public and special libraries, librarianship education, professional associations and publications, and recent developments including some special projects run by the state and NGOs.